Regional specific differentiation of integumentary organs: SATB2 is involved in α‐ and β‐keratin gene cluster switching in the chicken. Issue 9 (17th July 2021) - Lin, Gee‐Way; Liang, Ya‐Chen; Wu, Ping; Chen, Chih‐Kuan; Lai, Yung‐Chih; Jiang, Ting‐Xin; Haung, Yen‐Hua; Chuong, Cheng‐Ming
Abstract: Background: Animals develop skin regional specificities to best adapt to their environments. Birds are excellent models in which to study the epigenetic mechanisms that facilitate these adaptions. Patients suffering from SATB2 mutations exhibit multiple defects including ectodermal dysplasia‐like changes. The preferential expression of SATB2, a chromatin regulator, in feather‐forming compared to scale‐forming regions, suggests it functions in regional specification of chicken skin appendages by acting on either differentiation or morphogenesis. Results: Retrovirus mediated SATB2 misexpression in developing feathers, beaks, and claws causes epidermal differentiation abnormalities (e.g. knobs, plaques) with few organ morphology alterations. Chicken β‐keratins are encoded in 5 sub‐clusters ( Claw, Feather, Feather‐like, Scale, and Keratinocyte ) on Chromosome 25 and a large Feather keratin cluster on Chromosome 27. Type I and II α‐keratin clusters are located on Chromosomes 27 and 33, respectively. Transcriptome analyses showed these keratins (1) are often tuned up or down collectively as a sub‐cluster, and (2) these changes occur in a temporo‐spatial specific manner. Conclusions: These results suggest an organizing role of SATB2 in cluster‐level gene co‐regulation during skin regional specification. Key Findings: SATB2 switches sub‐cluster expressions of α‐ and β‐keratin. SATB2 causes ectodermal dysplasia‐like changes in feathers, beaks, and claws. SATB2 represses MMPs and activate collagen synthesis.